The feasibility of quarry dust powder suspension for surface modification of tungsten carbide cobalt - Yap, Ching Yee (2021)
Among composite materials, tungsten carbide cobalt (WC-Co) has a huge application in the industrial sector, especially in the mould and die industry. However, those mould and die material will wear out after some service time. Considering the hardness and high cost of WC-Co, most industries decided to dispose and buy new moulds and dies rather than repair them after wear. Thus, the surface modification of WC-Co is necessary to increase its lifespan and service time. In this study, the surface modification of WC-Co was done by using the electrical discharge coating (EDC) with quarry dust suspension. Before the experiment, the characteristic of quarry dust was investigated, which included the element composition and chemical compound, particle size and surface morphology. A Sodick AQ35L die-sinker EDM machine was used to conduct the EDC process. The effect of coating parameters (peak current (Ip) and pulse on time (Ton)) on the surface roughness, Vickers micro-hardness and layer thickness were investigated. A Respond Surface Methodology (RSM) matrix created by Minitab software was used to determine the parameter effects and the optimum parameters of this research. The quarry dust in different concentrations were compared and their effect to the characteristics of coated surface were also determined. The results show that the optimum parameters to achieve a hard surface, thick coating layer and low value of surface roughness were found to be at Ip = 4 A and Ton = 341 μs. Besides, the best coated surface finish without the micropores and microcracks can be obtained by using 10 g/l of quarry dust powder. Coating layer thickness was strongly affected by the quarry dust concentration. These results demonstrated the capability of reusing and recycling quarry dust as an environmental friendly coating material for surface modification of tungsten carbide cobalt (WC-Co) by using EDC process.